KEGIATAN PENGABDIAN PEMBUATAN FILM LONTAR PRASI UNTUK PELESTARIAN KEARIFAN BUDAYA LOKAL DI DESA TENGANAN PAGRINGSINGAN - I Nyoman Agus Suarya Putra; Putu Gede Surya Cipta Nugraha; Ni Wayan Wardani (Sewagati, 2023)
Lontar Prasi is an art that has grown and developed in Tenganan Pagringsingan Village in Karangasem, Bali since the time of our ancestors. Advances in digital technology in the current era are increasingly distancing this art from the younger generation. Other factors such as complicated prasi making, materials that seem ancient and primitive, wayang stories that are difficult to understand, text and illustrations that are less attractive, and their rare existence make it increasingly difficult for the younger generation and the public to get to know Prasi. By utilizing advances in digital technology to maintain the existence of Prasi, the film Lontar Prasi was made. The process of creating the Lontar Prasi film went through 3 stages, namely pre-production, production, and post-production. Evaluation of films is carried out by distributing questionnaires to content experts, media experts, and the public. The evaluation results of the Lontar Prasi film show that the content is quite good and worthy of publication as information media. With the Lontar Prasi documentary film Tenganan Pagringsingan Village, it is hoped that the community, especially the younger generation, will receive information and participate in preserving Balinese culture.